Newborn birth weight and its associated risk factors in Somalia using Somalia health and demographic survey - Denekew Bitew Belay; Nigussie Adam Birhan; Mahad Ibrahim Ali; Ding-Geng Chen (Global Pediatrics)
Background: Low birth weight is the result of fetal growth and it is a strong sign of infant morbidity and mortality. In sub-Saharan Africa, the number of low birth weight live births is estimated to have increased from 4.4 million in 2000 to 5 million in 2015. Low birth weight is a strong indicator of multifaceted public health problems, including unfavorable socio-demographic conditions, chronic illness, and poor health care during pregnancy. The aim of this study was to assess the prevalence and risk factors of newborn birth weight in Somalia. Methods: The data used for this study were obtained from the 2020 Somalia Health and Demographic Survey. A sample of 7462 newborn with their birth weight within five years preceding the survey was included. The newborns’ birth weight; which is first categorized in to three: low birth weight (<2.5 kg), normal birth weight (2.5–4 kg) and high birth weight (>4 kg), was considered as a response variable. The analysis was carried out using ordinal logistic regression and adjusted odds ratio with 95 % confidence interval and p-value <0.05 was used to declare statistical significance. Results: From the total of 7462 newborns include in the study, 1196 (16.03 %), 5304(71.08 %) and 962 (12.89 %) were born with low birth weight, normal birth weight and high birth weight, respectively. Maternal age (AOR = 1.48; 95 %CI: 1.12–1.956), having Antenatal care (ANC) visit (AOR = 1.24; 95 %CI: 1.09–1.41), gestational age ≥37 weeks (AOR = 2.02; 95 % CI: 1.34–3.03), rich wealth index family (AOR = 1.46; 95 %CI: 1.29–1.65) and mother with secondary/higher educational level (AOR = 1.51; 95 %CI: 1.19–1.92) as well as place of residence were significantly associated with higher birth weight. Conclusion: The results of this study showed that birth weight is significantly associated with mother age, ANC visit, mother educational level, wealth index, residence, and gestational age at birth. Significantly large proportions of newborn babies are born with low-birth weight and this might be duet to many factors. Since low birth weight is a strong indicator of multifaceted public health problem, the governmental and non- governmental organizations working on maternal health should focus on alleviating this public health burden by giving special attention for antenatal care utilization coverage and improve other maternal health.